#TITLE_ALTERNATIVE# - FEBRIANTI SYAFEI (NIM : 22214006), ANVI
Injection of low-salinity water (LSW) has widely been practiced because the water sources are available, environmentally friendly, and relatively cheaper among other practical advantages. Many coreflood tests have been published to address the low-salinity effect on waterflooding oil recovery. Most of the results showed that higher oil recovery could be obtained when the salinity of injection water is much lower than that of the formation water. Different mechanisms have been proposed to explain this low-salinity effect. However, there is no consensus about the dominant mechanisms. Thus, the research is made in order to determine the effect of salinity shock and varied ionic composition of the injection water (using synthetic brine) on oil recovery, the effect of clay content within the artificial loose sand core on oil recovery, and the most possible mechanisms behind the LS effect. From the study it is determined that (1) salinity shock gives additional oil recovery up to 25%; (2) in general, for this case, the concentration of clay does not give appreciable effect to the oil recovery; (3) ionic composition, especially cations such as Na+, gives significant increase in oil recovery; and (4) the most possible mechanism behind the incremental oil recovery gained from the experiment is a multi-component ion exchange (MIE).